Study the Effect of Exogenous Iodine on the Thyroid Transcription Factors during Pregnancy in Rat Model - Ghina Hamoodi Hussein; Ehab R. Muhssa; Alaa T. Shakir (Medical Journal of Babylon)
Background: This study was designed to evaluate whether a mother’s iodide supplement would be correlated with embryonic thyroid gland development. Objective: Thyroid transcription factors were be measured by an enzyme-linked immunosorbent assay technique in all studied samples. Materials and Methods: The study included three groups as follows: group 1: involved 20 adult female rats, and the animals in this group were administered distilled water and they served as control, group 2: involved 15 adult female rats, and the animals in this group were treated with a low dose of iodine (0.06 mg), and group 3: involved 15 adult female rats, and the animals in this group were treated with a medium dose of iodine (0.18 mg). After 18 days of pregnancy. The animals were sacrificed and the serum was collected to determine rat paired box protein (PAX8), rat Forkhead box protein E1 (FOXE1), rat Homeobox protein (Nkx-2.1) using enzyme-linked immunosorbent assay assay for the mother whereas the thyroid factors data were analyzed using SPSS (version 15.0). Statistical tests were conducted using SPSS version 26. The descriptive analysis (Mean ± S.E) and the significance were done using Duncan at P ≤ 0.01 (the significance level was 0.01 and the P-value was 0.05), respectively. P-value and significance level were (0.05) and (0.01), respectively. Results: Results reported the highest value in FOX1, NK2.1, and PAX8 concentration was in 1.8 gm followed by a concentration of 0.06 gm, whereas the lowest value recorded in control group was 224.49a ± 7.61 with significant differences at (P ≤ 0.05) between the studied groups in both mother and embryo, however. Conclusions: Depending on the obtained results, the current study found the thyroid transcription factors were involved directly with excess iodine taken.